2012
DOI: 10.1143/apex.5.126201
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Plasma-Induced Damage Distribution during Hole Etching of SiO$_{2}$ over Si Substrate by Fluorocarbon Plasma

Abstract: We have demonstrated an InP/InGaAs composite-channel metal-oxide-semiconductor field-effect transistor with a selectively regrown n þ -InGaAs source/drain formed by metal organic vapor-phase epitaxy. A 150-nm-long channel was fabricated using a dummy gate and by laterally buried regrowth in the channel undercut. The gate stack was formed after regrowth by replacing the dummy gate. The carrier density of the regrown layer was 4:9 Â 10 19 cm À3 . The maximum drain current at a drain voltage V d ¼ 1 V and a gate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…6 Results from a voxel-slab model, developed to investigate contact hole etching in SiO 2 , indicated that physical damage was reduced by maintaining a critical thickness of the overlaying polymer. 17,34 Bowing during the etching of HAR features was found to result from excessive fluxes of F and O radicals to the sidewalls according to the results of a line-of-sight profile simulator. 35 A model addressing pattern deformation and experimental measurements by atomic force microscopy indicated that the ratio of line width roughness to line edge roughness decreases with increasing etch depth, and the depth at which twisting occurs is shallower for a lower bias power.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…6 Results from a voxel-slab model, developed to investigate contact hole etching in SiO 2 , indicated that physical damage was reduced by maintaining a critical thickness of the overlaying polymer. 17,34 Bowing during the etching of HAR features was found to result from excessive fluxes of F and O radicals to the sidewalls according to the results of a line-of-sight profile simulator. 35 A model addressing pattern deformation and experimental measurements by atomic force microscopy indicated that the ratio of line width roughness to line edge roughness decreases with increasing etch depth, and the depth at which twisting occurs is shallower for a lower bias power.…”
Section: Introductionmentioning
confidence: 97%
“…These effects can be mitigated by carefully controlling the overlying polymer thickness through the gas flow rate and the over-etch time. 17,18 While being an etchant and providing activation energy, ions are also typically neutralized when striking surfaces on the top and inside of the feature. In doing so, positive charge is deposited on the surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Kuboi et al 22 . also demonstrated the time variation of damage distribution in the Si substrate during the SiO2 hole etching along with over-etching time using the string-slab model 21 as shown in Fig. 3.…”
Section: Modeling Methods For Etching Processmentioning
confidence: 98%
“…To calculate the damage depth distribution from the etched surface as well as the feature scale profile, a 2D string-slab model, an improved string model, was proposed by Kuboi et al 21 , 22 Figure 3. shows a schematic of the model with the surface reaction for SiO2 etching caused by ions and radicals.…”
Section: Modeling Methods For Etching Processmentioning
confidence: 99%
See 1 more Smart Citation